Photometric, polarimetric, and spectroscopic studies of the luminous, slow-decaying Type Ib SN 2012au. Issue 1 (24th August 2021) - Pandey, S B; Kumar, Amit; Kumar, Brajesh; Anupama, G C; Srivastav, S; Sahu, D K; Vinko, J; Aryan, A; Pastorello, A; Benetti, S; Tomasella, L; Singh, Avinash; et al.
ABSTRACT: Optical, near-infrared (NIR) photometric and spectroscopic studies, along with the optical imaging polarimetric results for SN 2012au, are presented in this article to constrain the nature of the progenitor and other properties. Well-calibrated multiband optical photometric data (from –0.2 to +413 d since B -band maximum) were used to compute the bolometric light curve and to perform semi-analytical light-curve modelling using the minim code. A spin-down millisecond magnetar-powered model explains the observed photometric evolution of SN 2012au reasonably. Early-time imaging polarimetric follow-up observations (–2 to +31 d) and comparison with other similar cases indicate signatures of asphericity in the ejecta. Good spectral coverage of SN 2012au (from –5 to +391 d) allows us to trace the evolution of layers of SN ejecta in detail. SN 2012au exhibits higher line velocities in comparison with other SNe Ib. Late nebular phase spectra of SN 2012au indicate a Wolf–Rayet star as the possible progenitor for SN 2012au, with oxygen, He-core, and main-sequence masses of ∼1.62 ± 0.15 M⊙, ∼4–8 M⊙, and ∼17–25 M⊙, respectively. There is a clear absence of a first overtone of carbon monoxide (CO) features up to +319 d in the K -band region of the NIR spectra. Overall analysis suggests that SN 2012au is one of the most luminous slow-decaying Type Ib SNe, having comparatively higher ejecta mass (∼ 4.7–8.3 M⊙ ) and kinetic energy (∼ [4.8–5.4] × 10 51 erg). Detailed modelling using mesa and the results obtained through stella and snec explosions also strongly support spin-down of a magnetar with mass of around 20 M⊙ and metallicity Z  = 0.04 as a possible powering source of SN 2012au.